Magnetic Properties of Cylindrical Diameter Modulated Ni 80fe20 Nanowires: Interaction and Coercive Fields - Escrig-Murua, J; Corona-Gonzalez, R (2013)
Magnetic properties of cylindrical Ni80Fe20 nanowires with modulated diameters are investigated theoretically as a function of their geometrical parameters and compared with those produced inside the pores of anodic alumina membranes by pulsed electrodeposition. We observe that the Ni80Fe20 nanowires with modulated diameters reverse their magnetization via the nucleation and propagation of a vortex domain wall. The system begins generating vortex domains in the nanowire ends and in the transition region between the two segments to minimize magnetostatic energy generated by surfaces perpendicular to the initial magnetization of the sample. Besides, we observed an increase of the coercivity for the sample with equal volumes in relation to the sample with equal lengths. Finally, the interaction field is stronger in the case of constant volume segments. These structures could be used to control the motions of magnetic domain walls. In this way, these nanowires with modulated diameters can be an alternative to store information or even perform logic functions. © 2013 The Royal Society of Chemistry.